SPECIFIC FEATURES OF LEGAL TERMS IN MODERN ENGLISH AND UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article studies the specific features of legal terms that are part of the terminological system. Their importance as a technical tool in jurisprudence is analyzed. Also financial reccomandations are offered regarding the technique of using terms in the field of law-making.